2018
DOI: 10.1002/chem.201706016
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Selective Heavy Metal Removal by a Novel Metal‐Organic Framework Designed with In‐Situ Ligand Building Block Fabrication Bearing Free Nitrogen

Abstract: Fast and effective adsorbents for the selective removal of Hg and Pb ions were prepared by the reaction of Zn(NO ) ⋅6H O, H BDC, and N ,N -bis(pyridin-4-ylmethylene) ethane-1,2-diamine (L) that yields an unprecedented two-dimensional layer-based supramolecular framework, {Zn(BDC)(L*)}⋅DMF (TMU-40), by solvothermal reaction. The formation of this framework involved an in situ C=C coupling of L to L* [L*=5,6-di(pyridin-4-yl)-1,2,3,4-tetrahydropyrazine]. As L* contains free nitrogen atoms, direct reaction of L* a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…Two‐dimensional MOFs, formulated as [Zn(BDC)(L 7 )] (TMU‐40) [BDC=1,4‐benzene dicarboxylate; L 7 =5,6‐di(pyridine‐4‐yl)‐1,2,3,4‐tetrahydropyrazine], was prepared to check selective removal of Hg II and Pb II ions from wastewater . Morsali et al.…”
Section: Adsorption Of More Than One Metal Ionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two‐dimensional MOFs, formulated as [Zn(BDC)(L 7 )] (TMU‐40) [BDC=1,4‐benzene dicarboxylate; L 7 =5,6‐di(pyridine‐4‐yl)‐1,2,3,4‐tetrahydropyrazine], was prepared to check selective removal of Hg II and Pb II ions from wastewater . Morsali et al.…”
Section: Adsorption Of More Than One Metal Ionmentioning
confidence: 99%
“… The suggestion mechanism for C=C coupling and cyclization reaction of L to L**. Adapted with permission from Ref . Copyright 2018, Wiley.…”
Section: Adsorption Of More Than One Metal Ionmentioning
confidence: 99%
“…The results demonstrated that the maximum values of 269 mg g −1 for Hg II were acquired in just less than 10 min without changes in the pH of the adsorption medium. These extremely fast kinetics, which were observed for TMU‐40, are able to reduce heavily contaminated water with the Hg II concentration of 40 ppm to the acceptable limit of 2 ppb for drinking water …”
Section: Strategies For Enhancing the Adsorption Performance Of Mofsmentioning
confidence: 99%
“…For instance, intra‐particle diffusion models based on the experimental data for TMU‐40 indicate that the adsorption process occurs in three different steps. The first step, with a high slope, shows the very fast adsorption of Hg II ions on the surface of the MOF, the second step is attributed to the entrance of metal ion into the pores, and the third step represents the equilibrium level …”
Section: Techniques Involved In Analyzing the Adsorption Behaviors Ofmentioning
confidence: 99%
See 1 more Smart Citation